"I Dream a World": Inclusivity in Choral Music Education. (December 2017) - Fuelberth, Rhonda; Todd, Christy
This article explores how choral music educators can facilitate access to meaningful music experiences for all students in their schools. In a changing landscape that honors equity and diversity, music education environments must also change to align with these values. To provide the optimal environment for successful inclusive practice, choral music educators should evaluate barriers to access in terms of scheduling, reconsider current curricular offerings, and imagine new solutions that support music learning for all students. Instead of structuring choral programs around traditional choral concerts and adjudications, directors can use the 2014 Music Standards and the framework of Universal Design for Learning to drive classroom content and acquire the flexibility needed to build inclusive classrooms.